Student Achievement Analysis: Implementation of Discovery-based Virtual Learning in Culinary Academy - Latifahtur Rahmah; Luthfiyah Nurlaela; Irra Chrisyanti Dewi (Universitas Negeri Makassar, 2021)
Organizing learning from home in an emergency of the spread of Covid -19. It requires educators to use creative learning models that focus on students, one of which is Discovery-based Virtual Learning (DVL). This study aims to analyze the effect of using DVL on student achievement. This study used a 2x2 factorial design. This research's data analysis technique is divided into two types, namely the prerequisite analysis test and hypothesis testing. The research results concluded that students who learn with DVL are significantly higher than Direct Instruction (DI). The next result is that students who have high initial knowledge get high learning achievement scores. Meanwhile, this study's results also showed a significant interaction between the learning model and initial knowledge of student achievement in foodborne disease competencies.